Barriers and enablers to help-seeking for common mental disorders among young people in low-income settings: Perspectives from Zimbabwe - Rufaro Hamish Mushonga; Tarisai Concilia Bere; Rebecca Jopling; Franklin Glozah; Maria Anyorikeya; Tiny Tinashe Kamvura; Suzanne Dodd; Arnold Maramba; Denford Gudyanga; Benedict Weobong; Dixon Chibanda; Melanie Abas; et al. (PLoS ONE, 2025)
Common Mental Disorders (CMDs), such as depression and anxiety are highly prevalent, particularly among young people globally. In Zimbabwe, contributing factors like poverty, unemployment, and the COVID-19 pandemic have exacerbated these challenges. Despite the pressing need for mental health support among young people, there remains a significant knowledge gap on barriers and enablers to help-seeking for CMDs among this demographic. This study addressed this gap by applying the Consolidated Framework for Implementation Research (CFIR) as an analytical framework to explore the unique factors influencing mental health help-seeking among young people in Zimbabwe. Methods We utilised a qualitative research design and conducted 32 semi-structured interviews with young people (15–24 years) across high schools and the Friendship Bench (FB) in Harare between 20 December 2022 and 30 September 2023. Interviews were audiotaped and transcribed verbatim and then coded using an inductive approach to capture patterns grounded in participants’ experiences. Thematic analysis was utilised to develop relevant codes and identify relevant themes. Results Nine themes were generated including six themes related to barriers (factors that hinder help-seeking for CMDs) and three themes related to enablers (factors that facilitate help-seeking for CMDs). Barriers identified include perceived stigma, privacy and confidentiality issues, unavailability of services, lack of awareness, financial challenges and lack of incentives. Enablers identified include raising awareness, implementing school based initiatives and enhancing accessibility and affordability of mental health services. Conclusion This study revealed significant barriers and enablers to help-seeking for CMDs among young people in Zimbabwe. Addressing these multifaceted barriers and leveraging the identified enablers is key to creating supportive systems that encourage young people in low-resource settings to seek and engage with mental health services, ultimately improving their mental wellbeing and overall quality of life.